PENGARUH METODE SSCS MENGGUNAKAN ALAT PERAGA MIND MAPPING TERHADAP HASIL BELAJAR MATEMATIKA SPLTV SISWA SMA DAR EL FIKRI KELAS X - Ratna Mayasari; Wahyu Setiawan (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
The purpose of this study is to find out the influence of the SSCS method using Mind Mapping props on the results of learning mathematics SPLTV. The research method used is class action research (PTK). Research is carried out in three cycles, each cycle consisting of planning, execution of actions, observation, and reflection. The subject of this study was conducted on class X students. The data collection techniques used are by tests and observations. Research data collection instruments are tests (pretest and posttest questions), and activity observation sheets. The study data was analyzed using a percentage test.  The study concluded that based on the results of preliminary tests and final tests of the increase in results of three cycles, namely pre-cycle (40%), cycle 1 (66.43%), and cycle 2 (77.86%).